Efficient human motion detection with adaptive background for vision-based security system - Kamaru Zaman, Fadhlan Hafizhelmi; Ali, Md Hazrat; Shafie, Amir Akramin; Rizman, Zairi Ismael (INSIGHT - Indonesian Society for Knowledge and Human Development, 2017)
Motion detection is very important in video surveillance system especially for video compression, human detection, and behaviour analysis. Various approaches have been used for detecting motion in a continuous video stream but for real-time video surveillance system; we need a motion detection that can provide accurate detection even in non-static background regardless of surroundings (outdoor or indoor), object speed and size, robust to camera noisy pixels or sudden change in light intensity. This is very important to ensure that the security of a monitored parameter or area is not compromised. In this paper, we propose a method for human motion detection that employs adaptive background subtraction, camera noise reduction and white pixel count threshold for real-time video streams.